CYTOKININ OXIDASE/DEHYDROGENASE3 Maintains Cytokinin Homeostasis during Root and Nodule Development in Lotus japonicus. Issue 2 (7th December 2015) - Reid, Dugald E.; Heckmann, Anne B.; Novák, Ondřej; Kelly, Simon; Stougaard, Jens
Abstract : A Cytokinin oxidase/dehydrogenase in Lotus japonicus regulates cytokinin levels to prevent inhibition of root growth and rhizobial infection during symbiosis. Abstract: Cytokinins are required for symbiotic nodule development in legumes, and cytokinin signaling responses occur locally in nodule primordia and in developing nodules. Here, we show that the Lotus japonicus Ckx3 cytokinin oxidase/dehydrogenase gene is induced by Nod factor during the early phase of nodule initiation. At the cellular level, pCkx3::YFP reporter-gene studies revealed that the Ckx3 promoter is active during the first cortical cell divisions of the nodule primordium and in growing nodules. Cytokinin measurements in ckx3 mutants confirmed that CKX3 activity negatively regulates root cytokinin levels. Particularly, tZ and DHZ type cytokinins in both inoculated and uninoculated roots were elevated in ckx3 mutants, suggesting that these are targets for degradation by the CKX3 cytokinin oxidase/dehydrogenase. The effect of CKX3 on the positive and negative roles of cytokinin in nodule development, infection and regulation was further clarified using ckx3 insertion mutants. Phenotypic analysis indicated that ckx3 mutants have reduced nodulation, infection thread formation and root growth. We also identify a role for cytokinin in regulating nodulation and nitrogen fixation in response to nitrate as ckx3 phenotypes are exaggerated at increased nitrate levels. Together, these findings show that cytokinin accumulation is tightly regulated during nodulation in order to balance the requirement for cell divisions with negative regulatory effects of cytokinin on infection events and root development.